The impact of agricultural production agglomeration on agricultural economic resilience: based on spatial spillover and threshold effect test - Ranran, Chao; Jingsuo, Li (Frontiers in Sustainable Food Systems, 2024)
This study focuses on the role of agricultural production agglomeration in strengthening agricultural economic resilience, exploring the threshold effect of agricultural technological innovation level and the spatial spillover effect of agricultural production agglomeration on agricultural economic resilience. We conducted research across 31 provinces (including autonomous regions and municipalities) in China from 2007 to 2022. By constructing the evaluation index system of agricultural economic resilience, the entropy value method is used to measure the value of agricultural economic resilience, and then kernel density estimation and spatial econometrics model, threshold regression model are used to analyze the relationship between agricultural production agglomeration, agricultural technological innovation and agricultural economic resilience. (1) The analysis of the spatiotemporal evolution trend shows that the overall level of China's agricultural economic resilience continued to rise, and presented a spatial development pattern of "high in the east and low in the west". The overall level of agricultural production agglomeration in China shows a trend of first rising and then falling, among which the level of agricultural production agglomeration in the central region is significantly higher than that in the northwest and southeast regions. ( 2) The spatial Durbin model shows that agricultural production agglomeration can not only effectively improve the level of local agricultural economic resilience, but also have a positive impact on neighboring agriculture economic resilience produces positive spatial spillover effects.(3) Agricultural production agglomeration can improve the level of agricultural economic resilience by promoting agricultural social service. (4) The impact of agricultural production agglomeration on agricultural economic resilience shows great differences in different geographical regions. Among them, agricultural production agglomeration in the central region has a significant positive impact on the agricultural economic resilience of both local and adjacent areas. (5) The threshold effect model shows that the impact of agricultural production agglomeration on agricultural economic resilience has significant nonlinear characteristics, and its impact shows an increasing marginal effect as the level of agricultural technological innovation increases.